Adolescents and parents’ perceptions of condom distribution in selected secondary schools in the high density suburbs of Bulawayo, Zimbabwe - Mudonhi, Nicholas; Nunu, Wilfred Njabulo; Ndlovu, Brighton; Khumalo, Nkosana; Dube, Oliver (Springer, 2021)
Condoms have been highlighted as one of the most effective strategies to prevent the spread of HIV and AIDS. This study assessed how adolescents and parents perceive the condom distribution programme in selected secondary schools in the high density suburbs of Bulawayo. A concurrent mixed method survey was conducted on three selected secondary schools. Three hundred adolescents and three hundred parents responded to a pre tested semi structured questionnaire. Likert scales were developed to assess knowledge and attitude levels. The χ2 test and multiple logistic regression were used to associate different demographic characteristics with attitudes and levels of knowledge regarding condom distribution at schools using STATA Version 13. Practices and beliefs were assessed using unstructured interviews on purposively selected adolescents and parents. Qualitative data collected was thematically analysed on MAXQDA. The response rate was 100% and 81% for adolescents and parents/guardians respectively. There were more females than males in both response groups. About 67% of adolescents and 60% of parents/guardians were knowledgeable about condom usage and its implications on prevention of spread of sexually transmitted infections and pregnancies. A large proportion of parents/adolescents (72%) had good attitudes towards condom distribution in schools compared to adolescents (27%). Age was strongly associated with knowledge in adolescents, with older adolescent 102 times more likely to be knowledgeable compared to younger adolescents. Religion was the strongest predictor of attitudes in parents/guardians with Catholic having an odds of 227. The concerned sexual health institutions should increase awareness among adolescents, targeting their attitudes towards condom distribution and usage. Targeting attitudes will hopefully foster safe sexual practices.